The Relationship between Income, Wealth and Age in Australia. (12th June 2019) - Tapper, Alan; Fenna, Alan
Abstract: This article analyses the relationship between income, wealth, wealth‐adjusted income and age in Australia using a 2009–10 cross‐sectional data set. The main findings are: (i) wealth and wealth‐adjusted income generally rise with age, while income is constant across the life cycle; (ii) both income inequality and wealth inequality rise until mid‐life and fall thereafter, while wealth‐adjusted income inequality depends on the method of calculation used, one showing a fall in later life and another showing no fall; and (iii) after income, wealth and wealth‐adjusted income inequalities are adjusted for age, underlying inequality is lower in all three cases.